Analisis Konsep Misi Social Gospel dan Relevansinya Bagi Misi Gereja Masa Kini - Yosep Belay (Sekolah Tinggi Teologi Intheos Surakarta, 2023)
Abstract. This article examines the concept of the the Social Gospel’ mission as a dialectical effort to find its relevance to the mission of the church today. Through this article the author presents the main ideas of the Social Gospel as a critique of the church's mission approach regarding social problems. The method used in this paper is a literature study. Through this study, the result is that Social Gospel theology which emphasizes the preaching of the Kingdom of God makes it against to conservative theology. However, the Social Gospel mission approach can be a critique to the conservative mission approach, so that the mission paradigm can be further expanded, not only paying attention to futuristic personal salvation, but also caring about social salvation today.Abstrak. Artikel ini mengkaji konsep misi Social Gospel sebagai usaha dialektik untuk menemukan relevansinya bagi misi gereja masa kini. Melalui artikel ini penulis mengemukakan gagasan pokok Sosial Gospel sebagai kritik terhadap pendekatan misi gereja terhadap permasalahan sosial. Metode yang digunakan dalam tulisan ini adalah studi literatur. Melalui studi ini diperoleh hasil bahwa teologi Social Gospel yang menekankan pada pemberitaan Kerajaan Allah membuatnya berseberangan dengan teologi konservatif. Meski demikian, pendekatan misi Social Gospel dapat menjadi kritik bagi pendekatan misi konservatif, sehingga paradigma misi dapat semakin diperluas, tidak hanya memperhatikan keselamatan pribadi yang futuristik, namun juga perduli terhadap keselamatan sosial pada masa kini.